2017
DOI: 10.1097/pcc.0000000000001182
|View full text |Cite
|
Sign up to set email alerts
|

Can the Pediatric Logistic Organ Dysfunction-2 Score on Day 1 Be Used in Clinical Criteria for Sepsis in Children?*

Abstract: Among children admitted to PICU with suspected infection, Pediatric Logistic Organ Dysfunction-2 score on day 1 was highly predictive of PICU mortality suggesting its use to standardize definitions and diagnostic criteria of pediatric sepsis. Further studies are needed to determine the usefulness of the quick Pediatric Logistic Organ Dysfunction-2 score on day 1 outside of the PICU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
54
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 23 publications
5
54
0
3
Order By: Relevance
“…Schlapbach et al demonstrated that PELOD-2 ≥ 8 best discriminated for both mortality and the composite outcome, while data on alternative pSOFA cut-points were not provided. This finding mirrors a prior study by Leclerc et al who also reported that PELOD-2 ≥ 8 best discriminated mortality in children with suspected infection [9]. Schlapbach et al reasoned that higher pSOFA/PELOD-2 thresholds would select for patients with multiple organ dysfunction syndrome but exclude children with single or more subtle organ dysfunction.…”
supporting
confidence: 78%
“…Schlapbach et al demonstrated that PELOD-2 ≥ 8 best discriminated for both mortality and the composite outcome, while data on alternative pSOFA cut-points were not provided. This finding mirrors a prior study by Leclerc et al who also reported that PELOD-2 ≥ 8 best discriminated mortality in children with suspected infection [9]. Schlapbach et al reasoned that higher pSOFA/PELOD-2 thresholds would select for patients with multiple organ dysfunction syndrome but exclude children with single or more subtle organ dysfunction.…”
supporting
confidence: 78%
“…Their median PELOD-2 score was significantly higher in the group who died than those who lived (died : survived = 13 : 3; P=0.0001). 20 We found that PELOD-2 score ≥ 8 lower prognostic value compared to other mortality predictors. Although it was not the best predictor of mortality, PELOD-2 score ≥ 8 was better than severe sepsis criteria based on diagnostic parameters.…”
Section: Discussionmentioning
confidence: 61%
“…The initial PELOD-2 validation study found that PELOD-2 scores were significantly higher in non-survivors compared to survivors [mean 14.9 (SD 6.1) vs. mean 4.2 (SD 3.2), respectively, P <0.0001]. 20 The study showed failure of three organ systems and a mean PELOD-2 score of 7.5 predicted a mortality rate of 7.1%. Whereas failure of three organ systems and mean PELOD-2 score of 11.5 predicted a mortality rate of 30.5%.…”
Section: Discussionmentioning
confidence: 86%
“…The new scoring criteria were developed and validated using a large cohort of >1 million adult patients (17). Although Sepsis-3 definitions were not validated separately for pediatric populations, recent studies have demonstrated the feasibility of developing pediatric SOFA (pSOFA) and Pediatric Logistic Organ Dysfunction-2 (PELOD-2) scores for use in pediatric patients (18,19). A fundamental challenge in creating consensus definitions for the pediatric populations is the degree of age stratification required for various organ dysfunction and laboratory parameters.…”
Section: Pediatric Sepsis Definitionsmentioning
confidence: 99%
“…A fundamental challenge in creating consensus definitions for the pediatric populations is the degree of age stratification required for various organ dysfunction and laboratory parameters. Further studies validating the utility of the pSOFA and PELOD-2 scores in pediatric populations are in motion, and it is hoped they will pave the way for the much-needed update in pediatric consensus definitions (19,20). Definitions for sepsis have important implications in assessing the impact of novel diagnostic tools on patient outcomes.…”
Section: Pediatric Sepsis Definitionsmentioning
confidence: 99%